Community college president’s perceptions of leadership during the COVID-19 pandemic - Hunke, Lori L. (Kansas State University, 2022)
Although campus crises have been an ever-present aspect of college life, they have been increasing in number and intensity. While disasters prompted many colleges to prepare crisis plans, the COVID-19 pandemic presented unique challenges. Effective and timely crisis leadership can affect the crisis outcome. By understanding the leadership styles and behaviors used in a crisis, it can inform best practices for handling future campus crises. The purpose of this qualitative case study is to explore how the COVID 19 pandemic affected leadership styles and behaviors of Midwestern community college presidents. The study is primarily driven by one question, what are Midwestern community college presidents’ perceptions of how their leadership and decisions had changed in response to the COVID-19 global pandemic. Study data were collected through semi-structured interviews and artifacts. The interviews were analyzed using thematic coding looking for common patterns and themes. The data were examined using a theoretical framework of interpretivism and symbolic interactionism. The conceptual framework incorporated crisis leadership styles, effective leadership competencies, and crisis leadership competencies within the context of community college governance and the COVID-19 crisis. The conceptual framework was to further understand how community college president’s leadership style and behaviors had changed in response to the COVID-19 pandemic. Community college presidents navigated the COVID-19 pandemic. Based on the study results, there are five recommendations for practice. The five recommendations are: prioritize safety of faculty, staff, students and the community; develop broad-based crisis management programs, encourage leaders to include mental health services in crisis planning, leverage crisis communications, and understand the criticality of connections.
Keywords: Community college president; Crisis leadership; Leadership style; COVID-19; Crisis management; Leadership characteristics or competencies